2022
DOI: 10.47985/dcidj.539
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Education in Pakistan: Role of Teachers’ Sense of Self-Efficacy

Abstract: The worldwide inclination toward inclusive education has made it possible for children with disability to be included in mainstream schools (Ozokcu, 2018). Inclusive education is regarded as a transformation that intends to remove all obstacles to the inclusion of every learner into the mainstream school system, irrespective of their disability (Hamenoo & Dayan, 2021). The idea of inclusion reflects a thoughtful approach that accepts, respects, and values diversity and differences among all individuals. It als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…The findings show that teachers' attitude towards mild learning disabilities is insignificantly related to inclusive settings in schools. According to the previous study, teachers have an adverse attitude towards learning disabilities if they are less severe, which is in agreement with previous research studies [5,22]. In the current research study, teachers were usually found to be more inclined towards including students with, for instance, physical and sensory disabilities compared to those with cognitive and learning disorders [17].…”
Section: Findings and Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The findings show that teachers' attitude towards mild learning disabilities is insignificantly related to inclusive settings in schools. According to the previous study, teachers have an adverse attitude towards learning disabilities if they are less severe, which is in agreement with previous research studies [5,22]. In the current research study, teachers were usually found to be more inclined towards including students with, for instance, physical and sensory disabilities compared to those with cognitive and learning disorders [17].…”
Section: Findings and Discussionsupporting
confidence: 91%
“…Earlier research studies also supported the finding that teachers have negative attitudes towards mild learning disabilities in comparison with sensory, physical, or behavioral disorders [19]. The reason for this reported by other researchers is that usually students with learning disabilities have multiple disabilities, therefore making them difficult to handle, and this is consistent in Pakistan [5]. The results are consistent with the current study, which is an indicator that there are some types of inadequacies regarding inclusive education.…”
Section: Findings and Discussionsupporting
confidence: 90%
See 3 more Smart Citations